DEGRADASI ETIKA BUSANA SEMBAHYANG UMAT HINDU - I Gde Widya Suksma; I Gusti Ketut Widana (UNHI PRESS, 2021)
Reflecting on the Balinese civilization in the past, it turns out that it is known, not because of the absence of no rma or past society ethics , which made most Balinese (Hindus) not wear complete clothes (especially without clothes), but simply because of the level of civilization at that time. such is the situation. The situation at that time was much influenced by the difficult economic situation , thus making the conditions of the Balinese people difficult . For example, the problem of food (welfare) is still very concerning. Especially for business clothing (clothes) looks all round economical, especially because of the limitations of k Capacity of . Do not be surprised if later on average apparel/ clothing is worn, both of men and woman. But when progress in various fields, especially the economy is getting better, new problems arise, not located in the completeness of fashion, but rather the occurrence of the phenomenon of ethical degradation of dress, especially when the people carrying out the event praying.